PERAN PAGUYUBAN PEDAGANG LOKAL SEKARAN DALAM MENGUATKAN EKONOMI KERAKYATAN DI KELURAHAN SEKARAN KOTA SEMARANG - Harto Wicaksono, Elly Kismini Asma Luthfi (Forum Ilmu Sosial, 2016)
The presence and development of modern retail franchises or village have now made the traditional business people, especially decreasing penghasilan.Kondisi grocer makes them form associations known as PPLS (Lokas Traders Association sekaran) .Artikel aims to explain role in consolidating haberdasher PPLS in order to withstand the competition with waralab and retail modern.Penelitian done with a qualitative approach that uses observation, interview and documentation as methods of data collection and data triangulation technique as the validity of the data. The results showed that the role and aktfitas PPLS in strengthening democratic economy is a way to accommodate the aspirations and be a forum for the existence of the local economy have now, become a media control over government policy and the relevant parties, be a place for people lokaluntukmengembangkan effort kelontongannya who coined competitiveness high with modern retail. The implications of the presence of PPLS this is the strengthening of solidarity grocer, the re-negotiation between local communities, government, and retail shop owners modern, growing awareness of the critical community could encourage the birth of a social movement, and the opening of the society's perspective on the strategy of strengthening and development of their economic activity,